Gemcitabine plus nab-paclitaxel in older patients with metastatic pancreatic cancer: A post-hoc analysis of the real-world data of a multicenter study (the NAPOLEON study). Issue 1 (January 2022) - Koga, Futa; Kawaguchi, Yasunori; Shimokawa, Mototsugu; Murayama, Kenichiro; Nakashita, Shunya; Oza, Noriko; Ureshino, Norio; Takahashi, Hirokazu; Ueda, Yujiro; Nakazawa, Junichi; Komori, Azusa; Otsu, Satoshi; et al.
Abstract: Objectives: This study aimed to examine the efficacy and safety of gemcitabine plus nab-paclitaxel (GnP) in older patients with metastatic pancreatic cancer (MPC), especially those ≥75 years old. Materials and Methods: This study retrospectively enrolled 153 patients with MPC who received GnP as first-line chemotherapy. Patients ≥75 years old were allocated to the older group, and those <75 years old were assigned to the non-older group. We compared safety, antitumor efficacy, and survival between the two groups. In the older group, prognostic indicators of survival were also assessed. Results: The pretreatment characteristics of the two groups were not significantly different excluding age, history of malignancy, and C-reactive protein levels. The initial dose and relative dose intensities of GnP were significantly lower in the older group. There were no significant differences in the adverse event and antitumor response rates between the two groups. Median progression-free survival and overall survival were 5.5 and 12.0 months, respectively, in the older group, versus 6.0 and 11.1 months, respectively, in the non-older group. In the older group, a Geriatric Nutrition Risk Index (GNRI) of less than 86 was associated with poor prognosis. Conclusion: GnP exhibited acceptable efficacy and safety in patients ≥75 years old with MPC. GNRI might be helpful for identifying older individuals at higher risk of unfavorable outcomes.